2020
DOI: 10.1177/1055665620954321
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel 3D-Printed Nasoalveolar Molding Appliance (D-NAM) on Improving the Maxillary Arch Dimensions in Unilateral Cleft Lip and Palate Infants: A Randomized Controlled Trial

Abstract: Objective: The aim of the current study was to introduce and measure the effectiveness of a new 3D-printed nasoalveolar molding (D-NAM) appliance on improving the maxillary arch dimensions (MADs) in infants with unilateral complete cleft lip and palate (UCLP) before surgical lip repair. Design: A prospective, balanced, randomized, parallel groups, single-blinded, controlled trial. Setting: All the steps of the current study were carried in the Department of Orthodontics, Cairo University in Egypt. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…These findings are in line with those of other authors who have demonstrated the difference in palate symmetry before cheiloplasty. 5,15,22 The analyses indicate improvement of palate symmetry between I-T' and I-T, at T2, due to the growth of the posterior region of the palate. 16 These data were consistent with the increase in parameters C'-T' and C-T and were congruous with those of other authors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These findings are in line with those of other authors who have demonstrated the difference in palate symmetry before cheiloplasty. 5,15,22 The analyses indicate improvement of palate symmetry between I-T' and I-T, at T2, due to the growth of the posterior region of the palate. 16 These data were consistent with the increase in parameters C'-T' and C-T and were congruous with those of other authors.…”
Section: Discussionmentioning
confidence: 93%
“…Considering that palate width is a negative predictor of palate development, 5,11,15,23,27 we emphasize the importance of further evaluation of cleft palate width. The proposal of a cleft width classification would contribute to determining the influence of cleft width on palate growth and treatment protocols.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…14,15 El-Ghafour et al and also Shen et al presented the application of molding appliance that improved the maxillary arch. 16,17 To our knowledge no previous description of 3D printing was published earlier.…”
Section: Introductionmentioning
confidence: 99%